The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1111/anae.13101
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative management of the obese surgical patient 2015

Abstract: SummaryGuidelines are presented for the organisational and clinical peri‐operative management of anaesthesia and surgery for patients who are obese, along with a summary of the problems that obesity may cause peri‐operatively. The advice presented is based on previously published advice, clinical studies and expert opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(82 citation statements)
references
References 115 publications
0
69
0
3
Order By: Relevance
“…High dose group = 4 mg.kg À1 ; middle dose group = 2 mg.kg À1 ; low dose group = 1 mg.kg À1 of sugammadex based on IBW. *Based on the AAGBI obesity guidelines [8]. The formulae for calculating LBW and ABW are those of Janmahasatian et al [18] and Gepts [19], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High dose group = 4 mg.kg À1 ; middle dose group = 2 mg.kg À1 ; low dose group = 1 mg.kg À1 of sugammadex based on IBW. *Based on the AAGBI obesity guidelines [8]. The formulae for calculating LBW and ABW are those of Janmahasatian et al [18] and Gepts [19], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, its dosage in morbidly obese patients should be based on weight lower than TBW [8]. Studies that have examined the reversal process using sugammadex in morbidly obese patients concluded that usual doses calculated from ideal body weight (IBW) are insufficient [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these investigations have evaluated primary outcomes during and after anesthesia[ 115 , 116 ]. Although efforts have been made to develop standardized guidelines or protocols for the anesthetic care of the obese patient[ 117 ], there is no known ideal anesthesia technique or drug combination. However, the introduction of enhanced recovery after surgery (ERAS) protocols after obesity-related and bariatric procedures has gained great acceptance[ 118 , 119 ].…”
Section: Immunomodulatory Effects Of Anesthetics In Obesitymentioning
confidence: 99%
“…Obese patients represent a diagnostic challenge for the surgeon, and require additional surgical preparation and time to assess anaesthetic and operative risks . Bariatric equipment and supplementary staff may also be necessary …”
Section: Introductionmentioning
confidence: 99%